NILAI PELANGGAN DITINJAU DARI KELAS MEREK DAN CITRA MEREK PADA PRODUK KOSMETIK - Rahayu Mardikaningsih; Samsul Arifin; Arif Rachman Putra; Misbachul Munir; Tri Seno Anjanarko (Jurnal Ilmiah Satyagraha, 2023)
Marketing Management is not only faced with increasingly strong business competition but also changes in consumer behavior. The development of technology and changes in lifestyle cause consumers to have dynamic behavior. Customer value is one of the consumer behavior that can change the direction of the company's marketing. All factors considered capable of influencing customer value were studied such as brand class and brand image. This research was conducted to determine customer value in terms of brand class and brand image. The study was conducted on 90 users of SKII brand facial care products. The research sample was obtained by purposive sampling which will then fill in the questionnaire which is the source of the data for this research. The data is processed by regression technique. The results of the study show that brand class influences the formation of customer value to consumers. The results showed that the brand class affects the formation of customer value to consumers. In addition, this study also shows that customer value can be developed by developing a brand image. Brand class together with brand image have been proven to build customer value to consumers